Orthodontic Treatment of Class III Malocclusion : A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Reported case of a 19 years old male, with Class III malocclusion, bilateral cross bite associated with anterior open bite, which was treated by fixed orthodontic treatment. After treatment there was a class I Molar and incisor relation as well as the open bite was corrected with accepted aesthetic and functional satisfaction of the patient. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15974 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 22-23